ALIRAN-ALIRAN ILMU FIQIH - ., Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2021)
Ushul Fiqh as the mujtahid's understanding of the Qur'anic texts and the As-Sunnah. That understandin varies with nash and level of knowledge as well as different skill specifications bring forth various streams in the fiqh tradition. The method of understanding is also used influence every stream of knowledge. The flow of mutakalimin arises from the understanding of the Qur'an and the Sunnah transmitted into the fiqh rules. While the flow of energy is basing its legalization through the events of that society and then he was drawn to the verse of the Quran and the Sunnah of the Prophet. End-to-end streams combine these two streams so that they appear symbiotically between the two. The study of the flow of fiqh usages is interesting to find out more comprehensive how this knowledge was developed and developed by the mujtahids.